Manfaat Pemahaman Algoritma Pemrograman Dalam Meningkatkan Kemampuan Pemecahan Masalah - Syasya Aisyah; Yahfizham Yahfizham (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2023)
An algorithm is a series of steps to solve a structured problem in a systematic and logical manner. Algorithms help solve problems quickly and accurately. In the modern era dominated by technology and computing, programming has become an inevitable skill in various aspects of life. One's success in solving technical and non-technical problems often depends on a deep understanding of programming algorithms. Algorithms are logical steps used to solve problems, and a solid understanding of algorithms opens the door to exceptional problem-solving abilities. This article will cover the basic concepts of algorithms, effective teaching methods, as well as case studies that demonstrate the real impact of understanding algorithms in improving problem-solving skills. This research aims to investigate the benefits that individuals gain in improving their problem-solving skills through understanding programming algorithms. The writing of this article uses the library research method. The result of this research is that there are many benefits gained from understanding algorithms in solving problems both in software and in the real world.